1998
DOI: 10.1063/1.869586
|View full text |Cite
|
Sign up to set email alerts
|

Decaying quasi-two-dimensional viscous flow on a square domain

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…[11][12][13] At early times, and at heights above the near-base region, the experimental data were found to exhibit excellent agreement with the streamfunction (19) and the corresponding velocity components defined by (21). Figure 6(a) shows a sample of streamlines from (19) compared with the streak line image already shown in Figure 2(a), from experiment C (at t = t * = 8.7 and z 0 /H = 0.329).…”
Section: The Inviscid Two-dimensional Starting Flowsupporting
confidence: 60%
See 2 more Smart Citations
“…[11][12][13] At early times, and at heights above the near-base region, the experimental data were found to exhibit excellent agreement with the streamfunction (19) and the corresponding velocity components defined by (21). Figure 6(a) shows a sample of streamlines from (19) compared with the streak line image already shown in Figure 2(a), from experiment C (at t = t * = 8.7 and z 0 /H = 0.329).…”
Section: The Inviscid Two-dimensional Starting Flowsupporting
confidence: 60%
“…Figure 6(a) shows a sample of streamlines from (19) compared with the streak line image already shown in Figure 2(a), from experiment C (at t = t * = 8.7 and z 0 /H = 0.329). Figure 6(b) shows measurements, also from experiment C, of the horizontal velocity component, v, extracted along the symmetry axis y = 1/2, plotted against x, and compared with the corresponding theoretical velocity profile defined using (19) and (21).…”
Section: The Inviscid Two-dimensional Starting Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-organization process strongly depends on the domain geometry and on the boundary conditions at the lateral walls, which play a fundamental role in the flow organization as they act as sources of vorticity and net angular momentum. 6 For instance, van de Konijnenberg et al 7 and Clercx et al 8 found that the final state of the self-organization process in a square container tends to be a single vortex with a size comparable to the domain. Maassen et al 9 studied the self-organization in rectangular containers and found a cell pattern of alternatesign vortices along the main axis.…”
Section: Introductionmentioning
confidence: 99%
“…If they are indeed constrained to verify no-slip velocity conditions on a closed boundary they can only be determined by numerical approach. The present paper regards the Stokes fundamental eigenmodes in the square whose physical implications are commented in [ 12] and illustrated in [5,6,22], for instance. Only one of them is known to the authors' knowledge, the most fundamental of all, whose symmetry properties are the most straightforwardly expected [5,22].…”
Section: Introductionmentioning
confidence: 99%